The Fascinating Mathematical Beauty of the Celebrity Conic Sections - Mulatu, Lemma,; Levett, E’Lona; Allard, Dustin (IJRDO -JOURNAL OF MATHEMATICS, 2018)
In this paper, we investigate some properties and applications of the three conic sections.